Liability on occupational safety and health care: the legal development from common employment to Occupational Safety and Health Act 1994 - Md Ismail, Che Thalbi (Global Academic Excellence, 2018)
The global economic recession some time ago made the occupational environment concern, left unattended. Further, this recession caused the unsecure and hazardous workplace, became common to society. Nevertheless, despite the above phenomenon, the fight for a perfect occupational safety and health system was always there. To claim for a compensation, a workman must establish that it is the employer’s fault which caused the injury. This shows that the principle still adopted the similar spirit with common law in Britain. The application of the common law principle did not really help the workmen in their claim, further, the safety and healthcare claim was considered as equivalent to other kinds of claims which was not given a separate platform. The ‘common employment’ doctrine, contributory negligence and assumption of risk, still strongly influence the court in making the decisions and restrict the workmen’s chances in getting the compensation. Hence, with the enactment of the Occupational Safety and Health Act 1994, the law has placed the liability on all the related parties, especially on the employer to safeguard the safety and health of workers. Besides that, the workers also will have the choices to make claim the tortious liability of the employer, or the involving parties be fined for breach of the statutory liability.